(untitled) (Journal of Food and Dietetics Research, 2023)
In view of their growing importance in human nutrition, incorporation of oats during the manufacture of short-dough type biscuits was studied. Rolled oats were incorporated at 25, 35 and 45% of refined wheat flour in short-dough type biscuit formulation. The oats incorporated dough exhibited less firmness as indicated by lower firmness value for 25% oats incorporation (21.73 N) as against 25.05 N for control dough measured by Texture Analyser. Sensory evaluation of biscuits prepared from the dough revealed that the biscuit made from 25% oat incorporated dough scored highest after control in most of the sensory attributes including overall acceptability. Sensory analysis indicated that oats incorporated biscuits scored less on body and texture owing to increased hardness and dry mouthfeel. The moisture and β- glucan contents were 2.94% and 0.7% for oats added biscuits (25% oats incorporation), respectively. It was concluded that good quality biscuits can be prepared by incorporating rolled oats in biscuit formulation.